1998
DOI: 10.1002/(sici)1097-0142(19980715)83:2<331::aid-cncr17>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of bcl‐2 in testicular carcinoma

Abstract: These findings revealed that bcl-2 expression occurs in GCTTs. Furthermore, they suggest that bcl-2 is associated with a more advanced malignant phenotype of this tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14] By contrast, decreased expression of MT-1 and MT-2 is related to poor prognosis in patients with prostate, testicular, and liver tumors. [15][16][17][18] In nonpathological tissue, MT-1 and MT-2 are mainly present in the cytoplasm. In rapidly proliferating cells, however, MT-1 and MT-2 are translocated to the nucleus from the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] By contrast, decreased expression of MT-1 and MT-2 is related to poor prognosis in patients with prostate, testicular, and liver tumors. [15][16][17][18] In nonpathological tissue, MT-1 and MT-2 are mainly present in the cytoplasm. In rapidly proliferating cells, however, MT-1 and MT-2 are translocated to the nucleus from the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Burger and colleagues compared parental NT2 teratocarcinoma cells with NT2 cells expressing human papilloma virus E6 protein and found no di erences in chemosensitivity (Burger et al, 1999). However parental NT2 cells express low basal levels of p53 relative to most other teratocarcinoma cell lines (Burger et al, 1999) and clinical studies of germ cell tumors have demonstrated a positive correlation between degree of nuclear p53 immunoreactivity and response to treatment (Eid et al, 1997). Therefore studies utilizing NT2 cells do not address the potentially important role of high level wild-type p53 expression for the sensitivity of teratocarcinoma cells to DNA damage.…”
mentioning
confidence: 99%
“…Chemostatic drugs are supposed to cause an inhibition or dysregulation of apoptosis [39]. Other mechanisms that have been implicated in the development of chemoresistance in cancers cells are modulation of enzymes involved in DNA repair [65][66][67], intracellular sequestration with metallothioneins [68], exocytosis in which proteins such as kinesins and dynines may be involved and modification of protein kinase C activity. These mechanisms are summarized in Fig.…”
Section: The Development Of Chemoresistancementioning
confidence: 99%